The Multifunctional Catalytic Hemoglobin from Amphitrite ornata: Protocols on Isolation, Taxonomic Identification, Protein Extraction, Purification, and Characterization - Anna L. Husted; Victoria R. Sutton; Lauren A. Presnar; R. Kevin Blackburn; Joseph L. Staton; Stephen A. Borgianini; Edward L. D’Antonio (Methods and Protocols)
The multifunctional catalytic hemoglobin from the terebellid polychaete Amphitrite ornata, also named dehaloperoxidase (AoDHP), utilizes the typical oxygen transport function in addition to four observed activities involved in substrate oxidation. The multifunctional ability of AoDHP is presently a rare observation, and there exists a limitation for how novel dehaloperoxidases can be identified from macrobenthic infauna. In order to discover more infaunal DHP-bearing candidates, we have devised a facilitated method for an accurate taxonomic identification that places visual and molecular taxonomic approaches in parallel. Traditional visual taxonomic species identification by the non-specialist, at least for A. ornata or even for other marine worms, is a very difficult and time-consuming task since a large diversity is present and the method is restricted to adult worm specimens. The work herein aimed to describe a method that simplifies the taxonomic identification of A. ornata in particular through the assessment of its mitochondrial cytochrome c oxidase subunit I gene by employing the DNA barcoding technique. Furthermore, whole-worm specimens of A. ornata were used to extract and purify AoDHP followed by an H2O2-dependent peroxidase activity assay evaluation against substrate 2,4,6-trichlorophenol. AoDHP isoenzyme A was also overexpressed as the recombinant protein in Escherichia coli, and its peroxidase activity parameters were compared to AoDHP from the natural source. The activity assay assessment indicated a tight correlation for all Michaelis–Menten parameters evaluated. We conclude that the method described herein exhibits a streamlined approach to identify the polychaete A. ornata, which can be adopted by the non-specialist, and the full procedure is predicted to facilitate the discovery of novel dehaloperoxidases from other marine invertebrates.